Outdoor Storage Characteristics of Single-Pass Large Square Corn Stover Bales in Iowa - Shah, Ajay; Darr, Matthew J.; Webster, Keith E.; Hoffman, Christopher (Iowa State University Digital Repository, 2011)
Year-round operation of biorefineries can be possible only if the continuous flow of cellulosic biomass is guaranteed. If corn (Zea mays) stover is the primary cellulosic biomass, it is essential to recognize that this feedstock has a short annual harvest window (≤1–2 months) and therefore cost effective storage techniques that preserve feedstock quality must be identified. This study evaluated two outdoor and one indoor storage strategies for corn stover bales in Iowa. High- and low-moisture stover bales were prepared in the fall of 2009, and stored either outdoors with two different types of cover (tarp and breathable film) or within a building for 3 or 9 months. Dry matter loss (DML), changes in moisture and biomass compositions (fiber and ultimate analyses) were determined. DML for bales stored outdoor with tarp and breathable film covers were in the ranges of 5–11 and 14–17%, respectively. More than half of the total DML occurred early during the storage. There were measurable differences in carbon, hydrogen, nitrogen, sulfur, oxygen, cellulose, hemi-cellulose and acid detergent lignin for the different storage treatments, but the changes were small and within a narrow range. For the bale storage treatments investigated, cellulose content increased by as much as 4%s from an initial level of ~41%, hemicellulose content changed by −2 to 1% from ~34%, and acid detergent lignin contents increased by as much as 3% from an initial value of ~5%. Tarp covered bales stored the best in this study, but other methods, such as tube-wrapping, and economics need further investigation.